THE INTELLECTUAL CAPITAL ON COMPANY GROWTH AND COMPANY VALUE WITH FINANCIAL PERFORMANCE AS AN INTERVENING VARIABLE IN THE AUTOMOTIVE INDUSTRY - Sri Utami Ady; Miftha Choirul Akbar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine the effect of Intellectual Capital with Financial Performance as an intervening variable on Company Growth and Company Value of the Automotive and Components Sub-sectors listed on the IDX. The population was 13 companies, and the sample was six with a purposive sampling technique. Analysis tools using Sem-PLS. The results showed that VAIC significantly influenced the company's financial performance. VAIC does not influence company growth. VAIC has a significant effect on firm value. The company's financial performance can mediate between VAIC and Company Growth with the status of the mediating result of Indirect-Only (complete mediation) significant and direct effects not substantial.